MODALITAS BELAJAR SEBAGAI PENDEKATAN INOVATIF DALAM MENINGKATKAN KUALITAS PEMBELAJARAN SISWA - Sance Yunita Kause; Sarci Faot; Theresia Tefa; Marla Kristin Manu; Kesia Indriani Taloim; Sofrida Ora; Maria Inriani Sesfao (CV. ADIBA AISHA AMIRA, 2025)
Learning modality is an essential component in developing innovative educational strategies aimed at improving students’ learning quality. Each student possesses a unique combination of sensory preferences visual, auditory, reading/writing, and kinesthetic which influences how they best absorb, process, and retain information. This journal explores the application of learning modalities as an innovative approach to personalize learning experiences, thereby enhancing student engagement and academic outcomes. Through a literature-based qualitative analysis, the study highlights the effectiveness of adapting instructional methods to suit different learning styles. The integration of diverse modalities not only fosters better comprehension but also cultivates a more inclusive and student-centered learning environment. Findings suggest that recognizing and responding to students' learning preferences is crucial for optimizing teaching strategies and achieving holistic educational development. This approach supports the shift from traditional, one-size-fits-all models toward more adaptive and meaningful pedagogies aligned with 21st-century learning demands.